Patient Satisfaction Level with Clinical Pathology Laboratory Services - Augi, Maulidiah Egi Saputri; Ni Luh Gede Puspita Yanti; Putu Ayu Parwati (CV. CENDIKIA JENIUS INDONESIA, 2025)
Background: Clinical pathology laboratory services play an important role in supporting diagnosis, treatment, and patient recovery. The quality of laboratory services affects patient satisfaction, which is a key indicator of hospital service quality. Objective: To determine the level of patient satisfaction with clinical pathology laboratory services at Hospital X in Denpasar. Methods: This research employed a descriptive design with a cross-sectional approach. A total of 80 outpatients aged 17–45 years participated, selected using accidental sampling. The instrument was a Likert scale questionnaire based on the ServQual dimensions (tangibles, reliability, responsiveness, assurance, empathy). Results: Overall, 78.8% of patients were satisfied. Satisfaction levels by dimension were: tangibles (80%), reliability (76.3%), responsiveness (77.5%), assurance (79%), and empathy (80%). Conclusion: Patients were generally satisfied with laboratory services. It is recommended that the dimensions of responsiveness and reliability need to be improved to enhance service quality.